The Effect of Internal Training and Obstacles to Music Teachers, Teaching Competency Improvement Effort - Pratama, Dicky Aji; Fathurrahman, Reza (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze and determine the competence of music teachers at Satsikmil Type A Pusdikajen Kodiklatad, as well as to find out the obstacles in improving the competence of music teachers and to find out what strategies are used to overcome these obstacles in an organization that has been established for a long time. By using descriptive research methods with a qualitative approach, as well as analyzing secondary data and direct interviews (in-depth interviews) to obtain primary data. The results showed that based on indicators of competence, namely knowledge, skills, and attitudes. The competencies possessed by military music teachers at Pusdikajen Kodiklatad are included in the fairly good category. Internal training is still not able to improve and improve the ability of military music teachers in the teaching and learning process, the limited number of trainers / Trainers who have adequate qualifications as educators in the field of technology (especially there are only a few people who master the Sibelius software)